The societal value of SARS-CoV-2 booster vaccination in Indonesia. Issue 11 (10th March 2023) - Johnson, Rob; Djaafara, Bimandra; Haw, David; Doohan, Patrick; Forchini, Giovanni; Pianella, Matteo; Ferguson, Neil; Smith, Peter C.; Hauck, Katharina D.
Abstract: Objectives: To estimate the expected socio-economic value of booster vaccination in terms of averted deaths and averted closures of businesses and schools using simulation modelling. Methods: The value of booster vaccination in Indonesia is estimated by comparing simulated societal costs under a twelve-month, 187-million–dose Moderna booster vaccination campaign to costs without boosters. The costs of an epidemic and its mitigation consist of lost lives, economic closures and lost education; cost-minimising non-pharmaceutical mitigation is chosen for each scenario. Results: The cost-minimising non-pharmaceutical mitigation depends on the availability of vaccines: the differences between the two scenarios are 14 to 19 million years of in-person education and $153 to $204 billion in economic activity. The value of the booster campaign ranges from $2, 500 ($1, 400-$4, 100) to $2, 800 ($1, 700-$4, 600) per dose in the first year, depending on life-year valuations. Conclusions: The societal benefits of booster vaccination are substantial. Much of the value of vaccination resides in the reduced need for costly non-pharmaceutical mitigation. We propose cost minimisation as a tool for policy decision-making and valuation of vaccination, taking into account all socio-economic costs, and not averted deaths alone.